Anniversary meeting: 30 November 1984 - -, - (Proceedings of the Society of Antiquaries of Scotland, 1985)
At the Anniversary meeting the Annual Report was delivered covering topics such as Membership, Meetings, Research and publications. The Treasurer also presented the report on the Society’s accounts. The Council reported to the Fellows on the plans for the future of the National Museum and the Society’s involvement in these plans. The Council for the following session was then elected and a list of Fellows who died during 1983-1984 was presented.